Evaluasi Safety Attitude Culture pada Perawat di Ruang Operasi PKU Muhammadiyah Gamping - Irma Wulandari; Titih Huriah; Sri Sundari (Universitas Batanghari Jambi, 2020)
In Indonesia, the incidence of medical error is quite high as evidenced by the existence of hospital incident reports, where in 2010 there were 75% of unexpected events and in 2011 as many as 60% of cases of surgical cases or patients with surgery. Medical error is one of the unwanted events, which occurred in various countries. Therefore it begins to develop a patient safety system. In order to carry out these functions, hospital should be able to carry out management based on customer oriented and patient safety by implementing a safety attitude culture. The purpose of this study was to determine the safety attitude culture evaluation of nurses in surgery rooms of PKU Muhammadiyah Gamping. This research was a research using a mixed methods research approach; namely a quantitative method with a descriptive approach and qualitative methods with a case study approach. The population in this study was nurses in surgery room with a total sampling technique of 20 people. The questionnaire in this study referred to the Surgery room Version of Safety Attitudes Questionnaire. Quantitative data analysis used descriptive analysis; while qualitative analysis was performed by data reduction, data presentation, and drawing conclusions/verification. The results shows that overall evaluation of safety culture attitude of nurses in the surgery room summed up in the high category (75,0 %). Meanwhile based on the safety attitude culture component, namely safety climate is in the high category (85,0%), team working climate is in the high category (90,0%), stress recognition is in the high category (65,0%), management perceptions is in the moderate category ( 75,0%), working conditions is in the high category (60,0%), job satisfaction is in the high category (90,0%).